Identification and recovery of local Vitis vinifera L. cultivars collected in ancient vineyards in different locations of Argentina. (26th May 2022) - Torres, R.; Aliquó, G.; Toro, A.; Fernández, F.; Tornello, S.; Palazzo, E.; Sari, S.; Fanzone, M.; De Biazi, F.; Oviedo, H.J.; Segura, R.; Laucou, V.; et al.
Abstract: Background and Aims: These last years, minor cultivars have gained attention as they provide an opportunity to offer original products in a global market and to combat global warming. Recent evidence brought to light the existing diversity within the group of autochthonous cultivars from Argentina and other South American countries, commonly known as criollas . The objective was to prospect, rescue and identify grapevine phenotypes recovered in ancient vineyards as putative criollas, in the western provinces of Argentina. Methods and Results: We collected 60 samples in 11 locations. Their identity and pedigree were analysed through nuclear simple sequence repeat (nSSR) markers. The 60 samples were grouped in 45 different genotypes, 19 of them corresponding to previously registered cultivars, while 26 were new genotypes, with no correspondence in international databases. The majority (18) of the 26 new genotypes were related with the criollas group while other genotypes presented a totally different genetic profile and its origin remains to be elucidated. Conclusions: The diversity within the South American cultivars is higher than previously thought. Ancient vineyards, located in isolated valleys, are reservoirs of minor cultivars, and growers have played a key role in maintaining and conserving them. Significance of the Study: This genetic diversity constitutes a valuable tool to explore alternatives for diversification and adaptation to climate change.